Plant species-specific rhizobiome assembly in the hyper-arid Atacama Desert - Fortt, J.; Castro-Severyn, J.; Choque, A.; Donoso, G.; Stoll, A.; Jones, D. L.; Saavedra, C. P.; Fuentes, B.; Remonsellez, F. (Frontiers in Microbiology, 2025)
The hyper-arid core of the Atacama Desert represents one of the oldest and driest regions of the world and is characterized by high aridity (precipitation <2 mm y−1), hypersaline soil conditions, extremes in temperature (−5 °C to 50 °C), intense UV irradiation and low organic matter content. Despite this, the Yungay area within the hyper-arid core is capable of supporting vegetation adapted to these extreme environmental conditions, including Distichlis spicata and Suaeda foliosa, which access deep groundwater resources. Little is known, however, about the below-ground microbial community that these plants support. To understand plant-microbe interactions in this environment, we investigated the physicochemical properties in the rhizosphere soils of D. spicata and S. foliosa. In addition, DNA was extracted from the rhizosphere soil and 16S rRNA gene amplicon sequencing performed to describe the taxonomic composition of the bacterial community. Our results revealed significant differences in the physicochemical properties between the rhizosphere soils of the two native plants. D. spicata showed higher Electrical Conductivity (EC), while S. foliosa had elevated ammonium concentrations. The microbial composition also varied between the plant species: Firmicutes (Bacillota), Proteobacteria (Pseudomonadota), Halobacteria, and Actinobacteriota (Actinomycetota) were dominant in both plant rhizosphere samples, but their relative abundance differed. In this context, Halobacteria were highly represented in the soils of D. spicata and Firmicutes (Bacillota) in those from S. foliosa. Furthermore, bacterial genera such as Enterococcus were only present in the S. foliosa rhizosphere, while Natrinema was highly represented in soil from under D. spicata (33.4%) in comparison to S. foliosa (1.5%). The microbial community of D. spicata was strongly influenced by EC, whereas that of S. foliosa correlated more with ammonium levels. These findings advance our understanding of microbial community adaptation in one of Earth’s most extreme environments and provide new insights into plant-microbe interaction in hyper-arid soils.